2011
DOI: 10.1074/jbc.m110.175174
|View full text |Cite
|
Sign up to set email alerts
|

Tethering Function of the Caspase Cleavage Fragment of Golgi Protein p115 Promotes Apoptosis via a p53-dependent Pathway

Abstract: The Golgi apparatus undergoes extensive fragmentation during apoptosis due in part to caspase-mediated cleavage of its structural proteins. Significantly, the Golgi-vesicle-tethering protein p115 is cleaved at Asp 757 early during apoptosis and the nuclear translocation of its 205 amino acid C-terminal fragment (CTF) precedes observable Golgi fragmentation. Nuclear localization of the p115 CTF induces apoptosis. The regulation of CTF nuclear translocation and the mechanism of its apoptotic activity however, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Nowadays, mechanism studies on the tumor apoptosis inhibition have drawn more and more attention. The studies on USO1 in mitosis and apoptosis revealed that USO1 was cleaved by caspase3 pathway and promoted cell apoptosis which is related to p53 signaling pathway [19,20]. Our results are consistent with the previous reports, but whether there are other proteins interacting with USO1 involved in cell proliferation and apoptosis in colon cancer still needs further research.…”
Section: Discussionsupporting
confidence: 94%
“…Nowadays, mechanism studies on the tumor apoptosis inhibition have drawn more and more attention. The studies on USO1 in mitosis and apoptosis revealed that USO1 was cleaved by caspase3 pathway and promoted cell apoptosis which is related to p53 signaling pathway [19,20]. Our results are consistent with the previous reports, but whether there are other proteins interacting with USO1 involved in cell proliferation and apoptosis in colon cancer still needs further research.…”
Section: Discussionsupporting
confidence: 94%
“…It was shown that expression of the CTF leads to the phosphorylation and stabilization of p53 and results in the expression of Puma. CTF expression also promotes p53-ERK interaction, which amplifies the apoptotic signal [152]. …”
Section: P53 and Apoptosismentioning
confidence: 99%
“…Caspase‐9 plays a major role in p53‐dependent apoptosis (Hakem et al, 1998; Kuida et al, 1998; How and Shields, 2011). We therefore investigated whether the caspase‐9 pathway was targeted by p53 in DNA‐damaging drug‐induced apoptosis sensitized by N‐myc in SHEP1 cells.…”
Section: Resultsmentioning
confidence: 99%